PENGARUH INFLUENCER MARKETING DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DENGAN E-WOM SEBAGAI VARIABEL MEDIASI - Ahmad Baendowi; Irawan Yuswono (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to examine the impact of influencer marketing and viral marketing on purchasing decisions for MS Glow products in Semarang City. This study also examines the role of electronic word of mouth (e-WOM) as a mediating variable in the relationship between the two variables.Method: A quantitative method was used by sending an online questionnaire to 192 respondents who had purchased MS Glow products at least twice in the past six months. The data were then analyzed using Structural Equation Modeling (SEM) to determine direct and indirect relationships among the variables.Results: showed that influencer marketing and viral marketing had a positive and significant impact on e-WOM, indicating that credible influencers and viral beauty content effectively stimulate online consumer conversations. Furthermore, both influencer marketing and viral marketing were found to directly influence purchasing decisions. Furthermore, electronic word of mouth (e-WOM) has been shown to mediate the relationship between the implementation of marketing strategy and consumer purchase behavior. These findings highlight the importance of combining persuasive influencer endorsement with organically spread viral content to generate trust-based social proof in the digital beauty market. Businesses are encouraged to collaborate with relatable influencers while encouraging user-generated viral content to reinforce positive e-WOM and drive purchase conversion more effectively. Keywords: e-WOM, Influencer Marketing, Purchasing Decisions, Viral Marketing